Nurse-doctor communication: A study on interprofessional communication - J.L. James (Curationis, 1984)
The health team is an ingenious concept, often defined as a group of people coming together and pooling their resources for the benefit of the patient. One immediately gets the impression of an interacting network of hospital staff, each sharing the belief that no one person can provide totally for any patient’s complex physical and mental needs.